The Contribution of Momentary Perspectives to Entrepreneurial Learning and Creativity. (December 2013) - Rae, David
This article explores how conceptualizing 'the moment' in entrepreneurship contributes to understanding entrepreneurial processes of learning and creativity. The significance of 'the aha moment' in entrepreneurial behaviour is widely used at a popular level but has not been well explored in relation to knowledge of human learning. The 'moment' is taken to be a point in time when we experience conscious mental awareness of what is going on and are able to generate meaning from this awareness, and to remember our thinking and responses. The aims of the article are: (a) to explore the connections between the concept of the moment in entrepreneurship and processes of learning and creativity; (b) to develop a framework that can be used to understand momentary perspectives in entrepreneurship; and (c) to explore the implications for entrepreneurial education and practice.